(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify a texture of internal rhythm, which is parallelism, as the research included a definition of it in the past and present, and then proceeding to talk about its types in the light of the poetry of the poet Miqdad Rahim, as the poet Miqdad Rahim employed parallelism in its various levels, whether in sound, sentences, or semantics. The most present of them is the vocal parallelism, as it serves the rhythm more than the other two types. As for the level of poetry, the free poetry had a remarkable presence because of its music of an organized rhythm and artistic aesthetic. As for the vertical poetry, it was His presence has more rhyme and rhyme than meaning. Because the language in it was often traditional and simple, and with regard to modern poetry, it had a special presence in the twin section because it relied on it in terms of rhymes whose different presence generates a rhythm that differs in the front of the verse from its inability, and thus generates an internal rhythm.